Evolution of Pt truncated octahedra to nanodendrites during the synthesis in methanol–water solution. Issue 12 (15th March 2021) - Zhou, Di; Han, Shaobo; Li, Yong; Ta, Na; Zhou, Yan; Li, Mingrun; Miao, Shu; Shen, Wenjie
Abstract : The size and shape of the Pt particles could be tuned from truncated octahedra (3.5 nm) to nanodendrites (13.5 nm) by simply varying the CH3 OH/H2 O ratio in the synthetic solution. Abstract : The size and shape of Pt nanoparticles largely determine the surface atom arrangements and the electronic properties. The control of particle size and shape heavily relies on the nucleation and growth rates of Pt crystals, which are intimately associated to the synthetic conditions. Here, Pt truncated octahedra and nanodendrites were fabricated by reducing Pt 4+ cations in a methanol/water mixture using PVP as the capping agent, where the shape mediation of Pt particles was done by simply varying the methanol/water ratio. The structure evolution of the intermediate products during the synthesis was monitored by UV-Vis spectroscopy and TEM/STEM. It was found that methanol-rich solution induced fast reduction of Pt 4+ cations and isotropic growth of Pt crystals into truncated octahedra, whereas water-rich solution led to a slow reduction of Pt species and continuous nucleation in the initial stage and fast autocatalytic growth and oriented attachment during the later stage, forming highly branched nanodendrites.